File System Concepts in Minimal Biological Systems - Ackovska, Nevena; Bozinovski, Stevo; Jovanchevski, Gjorgji (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2008)
This paper elaborates on different organizations of the files in the genetic systems. These organizations of the file system are also detected in the human created file systems. They include different groupings of genes related by similarity, tasks, segmentation and packing. The other part of this paper elaborates on another important concept, the concept of genomes: set of all genes of specie. There are some valuable lessons that could be learned by observing how the nature handles its file system.